Co-Delivery of 5-Fluorouracil and Paclitaxel in Mitochondria-Targeted KLA-Modified Liposomes to Improve Triple-Negative Breast Cancer Treatment - Tianyu Chen; Hui Chen; Yichun Jiang; Qi Yan; Shuling Zheng; Min Wu (MDPI AG, 2022)
In this research, KLA-modified liposomes co-loaded with 5-fluorouracil and paclitaxel (KLA-5-FU/PTX Lps) were developed, and their antitumor activity against triple-negative breast cancer (TNBC) was evaluated. KLA-5-FU/PTX Lps were prepared using the thin-film dispersion method, and their in vitro anticancer efficacy was assessed in human breast cancer cells (MDA-MB-231). An MDA-MB-231 tumor-bearing mouse model was also established to evaluate their antitumor efficacy in vivo. KLA-5-FU/PTX Lps showed enhanced cytotoxicity against MDA-MB-231 cells, improved drug delivery to mitochondria, and induced mitochondria-mediated apoptosis. The modified liposomes also showed favorable antitumor activity in vivo due to their strong ability to target tumors and mitochondria. The liposomes showed no obvious systemic toxicity. Our results suggest that KLA-5-FU/PTX Lps are a promising system with which to target the delivery of antitumor drugs to mitochondria as a treatment for TNBC.